Implementation of Problem Posing Learning using PhET Interactive Simulations to Improve Physics Learning Outcomes of XMIPA1 Students MAN 1 Medan - Afandi, Herry (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this classroom action research is to use PhET Simulation technology combined with problem posing learning models to improve physics learning outcomes for XMIPA1 at MAN 1 Medan. This type of research is a class action research using Kemmis-Mc Taggart designs, which begins with the observation of the daily test scores for Physics XMIPA1 with a class average score of 72.82, which means that it’s still below the minimum completeness criteria (KKM), which is ≥80. The research was conducted on 36 students in class XMIPA1 MAN 1 Medan in the odd semester of the 2022/2023 Academic Year. The Problem Posing Learning Model emphasizes the formulation of simple problems or reformulation of existing problems in several ways in order to solve complex problems so that they can be solved. PhET simulation parabolic motion material has a parabolic motion simulation which is expected to increase students understanding in exploring the concept of parabolic motion. Methods of collecting data through observation, documentation, post-test, and interviews. The percentage of student learning outcomes in pre-cycle activities to cycle 1 experienced an increase from 64.28% to 82.48% with an N-gain value of 0.328 in the moderate category. Then the learning outcomes increase from cycle 1 to cycle 2, namely to 88.28% with the result of obtaining an N-gain value of 0.368, which means an increase in the medium category. So that the problem posing learning model with PhET simulation can improve physics learning outcomes in XMIPA1 class at MAN 1 Medan odd semester 2022/2023.